The Veterinary diagnostic procedures manual Dr. Dolores R. Dalusong, Laboratory Services Division, Animal Health Division and the Philippine Animal Health Center of the Bureau of Animal Industry. - Dalusong, Dolores R. (Bureau of Animal Industry, Department of Agriculture, 1992)
It is intended for animal diagnostic laboratories to assist veterinarians in the preparation and preservation for transport of specimen for laboratory testing. It is also meant to help livestock personnel in proper treatment and disease prevention measures in animals.